13 CANCER-ASSOCIATED THROMBOSIS AND THROMBOCYTOSIS: THE EDOXABAN SOLUTION. (15th December 2022) - Fioretti, Agnese Maria; Leopizzi, Tiziana; Giotta, Francesco; Luzzi, Giovanni; Oliva, Stefano
Abstract: Introduction: TEV is the second highest cause of death in malignancy with 20% incidence. Platelets is a leading mediator of thrombosis as well as of tumor development. Indeed, thrombocytosis is a predictive biomarker of thrombosis risk and contributes to CAT burden. However, the management of thrombocytopenia in patients with CAT is well investigated, whereas evidence is poor on the management of patients with concomitant occurrence of thrombocytosis and CAT. Case report: A 67 y-o woman, in primary thromboprophylaxis with 100 mg/die aspirin for myeloproliferative syndrome (PC: 771 x10 3 /µl), was treated with left mastectomy for infiltrating ductal carcinoma (G3 pT1cN1a Mx Ki67:25%) and adjuvant chemotherapy with anthracyclines and anastrozole. Due to bone metastases, zoledronic acid, fulvestrant and palbociclib were administrated. For liver metastases, she was treated with exemestane, paclitaxel and bevacizumab and for disease progression, started capecitabine and cyclophosphamide, still ongoing. She experienced left jugular vein thrombosis (Fig 1-2) treated with edoxaban 60 mg/die with an almost total DVT regression after 2 months. The multidisciplinary team (oncologist, cardiologist, hematologist) decided to interrupt aspirin, proceeding antithrombotic therapy with edoxaban full dose. Concomitant cytoreductive therapy with hydroxyurea was started concomitantly with edoxaban. PC was reduced (522 x10 3 /µl). After 1-month follow-up duplex ultrasound still documented mild persistence of the DVT (Fig 3-4), the patient was compliant and the anticancer regimens (addressed to both the solid cancer and the hematologic disease) were still administrated without any adverse effects. Conclusions: CAT is a frequent and major complication of malignancy, worsening mortality, morbidity and decision-making. Platelets play a central role in promoting the hypercoagulable melieu of cancer as well as the metastases growth. Notably, thrombocytosis occurrence further increases the thrombogenic burden in malignancy; nevertheless, its concomitant development together with CAT is understudied. In the reported case, a solid tumor, together with hematologic cancer and DVT, concurred to a difficult management of a patient admitted to our multidisciplinary team. The use of a DOAC, edoxaban, at full dose, without concomitant therapy with aspirin, was an effective, safe and manageable antithrombotic treatment option, allowing the continuation of anticancer agents with no interruptions or delays. The knowledge of tumor-specific pathways may help to personalize strategies for CAT prevention. Fig 1-2 Fig 3-4